The microbial mechanism of maize residue decomposition under different temperature and moisture regimes in a Solonchak - Fan Huang; Wan Zhang; Lihua Xue; Bahar Razavi; Kazem Zamanian; Xiaoning Zhao (Scientific Reports)
Abstract Soil salinization becomes serious under climate change and human activities. Although the residue decomposition contributes lots to soil carbon storage and fertility, the decomposition process and microbial mechanisms on saline-alkali soils are still vague facing climate change. We measured the mass loss of residue (0, 4, 8, 15, 30, 60 and 90 days), CO2 emission (every two days), and the microbial community structure (0, 4, 15 and 90 days) by using the litter bag method, gas chromatography and high-throughput sequencing technology during the residue decomposition (90 days) in a saline-alkali soil from the Tarim River Basin, China under various temperatures (15 °C, 25 °C, 35 °C) and soil moisture levels (20%, 40%, 60% water holding capacity). The decomposition stage consisted of fast (0–15 days) and slow periods (15–90 days). Using the double exponential equation, the decomposition rates of labile and recalcitrant components, the labile component and cumulative CO2 emissions increased faster with increased moisture than with temperature. The Q10 was greater at 15–25 °C than at 25–35 °C, which increased with the increased soil moisture in the leaf but with decreased soil moisture in the stem at 15–25 °C. Proteobacteria increased from 0 to 15 days on leaves (25–43%) and stems (25–29%) and showed no changes thereafter. Proteobacteria increased with increased soil moisture but decreased temperature. Actinomycetes was the opposite and more abundant on the stem than on the leaf. Bacteroidetes increased after 15 days and increased with increased soil moisture. Firmicutes were the main bacterial groups at 0–15 days, but decreased at 15–90 days (leaf: 44 − 15%, stem: 49 − 13%). In conclusion, warming, especially 15–25 °C, contributes to the decomposition of stems and wetting, especially 20-40% WHC, contributes to that of leaves within the first 15 days, afterwards wetting played an important role. Our results could also provide the adopting strategies for residue return to increase the soil carbon content while decreasing CO2 emissions facing climate change.